Photocatalytic degradation of methylene blue and methyl orange in a Zn(II)-based Metal–Organic Framework. Issue 38 (14th August 2016) - Wang, Chong-Chen; Zhang, Yan-Qiu; Zhu, Tian; Wang, Peng; Gao, Shi-Jie
Abstract: A novel 3D Zn(II)-based metal-organic framework [Zn2 (odpt)(bpy)(H2 O)](bpy)0.5 (1 ) (H4 odpt = 4, 4′-oxidiphthalic acid, bpy = 4, 4′-bipydine) has been hydrothermally synthesized, and characterized by the single-crystal X-ray diffraction, Fourier transform infrared spectroscopy, UV–vis diffuse spectrum, and thermal gravimetric analysis. Compound1 shows highly efficient photocatalytic activity on the degradation of individual methylene blue (MB) and methyl orange (MO), while exhibits a preferential photocatalytic degradation of MO in the MO/MB mixture under UV light irradiation. The possible photocatalytic mechanism was proposed, which was confirmed by trapping experiments of radicals via the addition isopropanol as radical scavenger, and compound1 exhibits excellent recyclability and stability, which can achieve good degradation efficiency to MB for five runs.